Immune profiles according to EGFR mutant subtypes and correlation with PD-1/PD-L1 inhibitor therapies in lung adenocarcinoma - Koh, Young Wha; Park, Bumhee; Jung, Se Hee; Han, Jae-Ho; Haam, Seokjin; Lee, Hyun Woo (Frontiers in Immunology, 2023)
Background: We examined the distributions of 22 immune cells and responses to PD-1/PD-L1 inhibitors according to EGFR mutation profile in three independent LUAD datasets. Methods: We used CIBERSORTx to analyze the distributions of immune cells and tumor immune dysfunction and exclusion (TIDE) or tumor mutation burden (TMB) to analyze responses to anti-PD-1/PD-L1 therapy in two public LUAD datasets. The results were verified with a validation set including patients treated with PD-1/PD-L1 inhibitor. Results: Compared to EGFR mutants, EGFR wild-type had higher numbers of CD8+ T cells, CD4 memory activated T cells and neutrophils, and lower numbers of resting dendritic cells and resting mast cells in two datasets. In subgroup analyses, CD8+ T cells, CD4 memory activated T cells were more numerous in EGFR rare variant than wild-type, L858R and exon 19 deletions. In TIDE or TMB analyses, EGFR rare variant was predicted to respond better to PD-1/PD-L1 inhibitor than wild-type, L858R and exon 19 deletions. In the validation set verified by immunohistochemical staining, levels of CD8+ T cells in the EGFR rare variant or wild-type was significantly higher than in EGFR L858R and exon 19 deletion. In patients treated with PD-1/PD-L1 inhibitor, the survival rate of EGFR wild-type and rare mutant was higher than that of L858R and exon 19 deletion. Conclusions: The EGFR rare mutation shows a high immune activation state compared to wild-type, L858R and exon 19 deletion, indicating it as a target for PD-1/PD-L1 inhibitor therapy.